Jews or Germans? The Breslau's Cultural Background of Edith Stein. - Rybińska, Agata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
This article is devoted to Edith Stein's background in Breslau. The basic sources are the texts of Edith Stein and Suzane Batzdorf, aided by the author’s own research on the life of the Jewish Community in Wrocławin the 19th and 20th century. The main issue addressed in the paper regards the extent to which Edith Stein’s life was influenced by the Jewish and German societies. Importantly, her education was not religious and her friends along with some family members were secularised. The identity of Breslau's Jews was complex; even though they were not multilingual, yet certainly multicultural, having been Jews and Germans at the same time. This variety was the keynote of Stein’s background. The question therefore should not be formulated as‘Jews or Germans?’ but rather how much Jewish and how much German they were? The answer is as complicated as their complex identity.